Anther wall development and structure in wild tomatoes (Solanum sect. Lycopersicon): functional inferences - Carrizo Garcia, Carolina (2006)
Development of the anther wall and its structure at maturity in wild tomatoes (Solanum sect. Lycopersicon) are described, and the features are discussed in relation to anther dehiscence and the buzz-pollination mechanism. The anther wall formation follows two different patterns in the same microsporangia and a high number of cells divisions may occur. The number of layers formed varies across the ventral, dorsal and lateral surfaces of each theca. Large epidermal cells develop, lining the stomium, and they could possibly be involved in stomium opening. Cells with thickenings are formed in the apical fifth of the anther, where the tissues seem to degenerate after the stomium opening, forming a wider aperture through which the pollen can be shed. The multilayered dorsal wall remains swollen and could act as an attractant to pollinators and as mechanical support. The apparently disordered anther wall development sets up different structures across and along the anther, which can be interpreted as histological adaptations to the buzz-pollination Mechanism.